Um método para modelagem de controle de AMS usando redes de Petri virtuais - Araújo, Rodrigo Guimarães (2006)
An Automated Manufacturing System (AMS) is a production system where a discrete number of raws is processed and assembled by controlled machines and/or robots. Controlling AMS is a complex task, due to the several sub-systems that compose it and the need for attending strategic production issues and market. The AMS control complexity increases with the necessity of production and technologic resources. The studies related to AMS control normally consider specific features of the system. Some authors propose solutions considering architecture, some others consider approaches by modular nets, others consider mathematic analysis; and so, each study has its contribution in a specific point. This work considers a wider set of features related to the problem of modeling AMS control. It is presented different options of architecture, different ways to concern hierarchically about the problem, the use of Petri Nets as a way to represent graphically the problem conserving the mathematic formalisms, simulation, and the use of a graphic software that treat all the options before. The proposal of this work is indicate a modeling method for AMS control that considers all features related to its control. This method proposes eight elaboration stages of the model. The stands consider the elements in a specification level more generic and, gradually, they are more detailed. In some stands, simulations are applied with the objective of validate what has been modeled. The work ends with the application of the method to a hypothetic FMS. It is considered a production planning for five types of products in determined quantities. The method application is considered effective, since trough the simulation of the model, it can be verified that all the products are produced according to the production plan proposed and that eventual deadlocks and conflicts can be avoided.